中國大陸部分大學教育學院遭裁撤整併之研究 The Revocation and Consolidation of College of Education in Some Chinese Universities - 周祝瑛 Chuing Prudence Chou; 馬冀 Ji Ma (Higher Education Foundation, 2017)
2015年底，中國大陸官方公布「雙一流」計畫，意在統籌推進世界一流大學和一流學科之建設；隨後，部分大學教育學院及高等教育研究所遭到裁撤。有鑑於此，本研究擬從國際和臺灣教育科系的發展變化出發，結合民國時期、1949年之後及近20年來教育科系的發展與整併歷程，探討近年來中國大陸知名大學裁撤教育學院之原因，進一步歸納出問題之癥結出在雙一流政策指引、師資供需失衡、大學功利主義導向、領導非理性決策等因素，造成知名大學教育學院與科系的裁撤現象。 In the end of year 2015, the "Double First-Rate" (DFR) plan published by Mainland China government aimed at advancing Chinese universities and subjects to reach the world-class standard. Meanwhile, some leading universities either abolished or merged their education college or Institute of higher education in order to compete for the DFR plan. This paper started with the development and change of education department from international and Taiwan perspectives, coupled with the historical development of Chinese education department before and after 1949 and the last two decade. It was found that the reason of such re-structuring among Chinese leading universities' education college may derive from pressure of the current DFR policy orientation, unbalanced teachers supplydemand relationship, market-driven orientation and other non-rationality leadership.